NUTRITION GAMES AND INVENTIVENESS OF PRACTITIONERS/CHILDREN - Maria da Glória Pinheiro Rezende; Eliane de Abreu Soares; Inês Barbosa de Oliveira (Universidade do Estado do Rio de Janeiro, 2017)
In this article we aim to make visible the practitioners/children "performing arts" in a practical/experience of the daily life of the "Body, Color and Flavor" workshop at the Leblon Art Center of Rio de Janeiro Municipal Department of Education. The purpose of this workshop is to discourage thought/performed curricula, as well as the networks of knowledge, actions, values and beliefs in food, nutrition and health of practitioners/children in the third grade of elementary education. In this methodological path, we are guided by the thoughts of Paulo Freire, Certeau, Nilda Alves, Carlo Ginzburg, Inês Barbosa de Oliveira and Boaventura de Sousa Santos. To cheat the rules and to invent other ways of playing educational games are the schemes of children who do not recognize themselves in prescriptive and normative educational strategies.By subverting and re-signifying official artifacts, practitioners/children produced thought/performed curricula in everyday school settings. By making these doings/knowledge visible,we hope that we can instigate the exercise of the ecology of knowledge in the elaboration of these instruments and in the educational practices inside/outside schools. DOI: 10.12957/demetra.2017.28674